Creativity in Meaning Construction and Translation – A Cognitive Perspective on the Humurous Language Used by Big Friendly Giant in Roald Dahl’s the BFG in its English, Polish and Portuguese Versions - Klos, Sylwia (Research in Language, 2024)
The paper explains how our mind creates a meaning in a wordplay. The model of mental maps (Author, 2020) based on the theory of conceptual blending (Fauconnier,1997, Fauconnier & Turner, 2002) and the geneplore model based on the theory of creative cognition (Finke, et al, 1992) presented in the paper describe the operations in the mind related to generating, exploring and transforming ideas and/or linguistic and non-linguistic units that result in the emergence of a new meaning embedded in the wordplay. To illustrate the cognitive processes in meaning construction, the paper refers to the humorous language of Big Friendly Giant in Roald Dahl’s The BFG in its original English version as well as its translations into Polish and Portuguese.